Deep Provisions in Regional Trade Agreements: How Multilateral-friendly? An Overview of OECD Findings - Lejárraga, Iza (OECD Publishing, 2014)
Over the past decade, an increasing number of economies have resorted to regional trade agreements (RTAs) as a means to further the market-opening and rule-making agenda. In this context, this paper addresses the question as to whether and how selected elements of RTAs could be used as 'stepping stones' for multilateralisation in the future. The report synthesizes the OECD work on RTAs by examining regional provisions that deepen (WTO-plus) and expand (WTO-beyond) multilateral commitments across a broad range of policy areas. It finds that WTO-plus measures are becoming more widespread and similar over time, suggesting that there may be growing receptivity and preparedness to endorse higher levels of commitments. The report distils a set of attributes that may be able to render WTO-plus provisions more amenable to multilateralisation, either through a bottom-up (RTA-driven) or top-down (WTO-driven) approach. It considers the degree of convergence, homogeneity, discrimination, enforceability and economic impact of selected measures in RTAs, with a view to moving towards a shared understanding of multilateral-friendly practices that can be promoted in regional negotiations
Keywords: Trade